In pursuit of progress : narratives of development on a Philippine island - Bulloch, Hannah C. M. (Southeast Asia--politics, meaning, memory., 2017)
'In Pursuit of Progress' explores how meta-narratives of development become entangled in people's identities and life trajectories; how they weave their way into people's imaginings of their histories, their understandings of their place in the world, and their dreams for their future.